A review of research on outward foreign direct investment from emerging countries, including China: what do we know, how do we know and where should we be heading?. Issue 1 (1st January 2018) - Paul, Justin; Benito, Gabriel R. G.
Abstract: Using the Antecedents, Decisions and Outcomes (ADO) format as an organizing framework, this article gives an overview of the literature on different dimensions and characteristics of outward foreign direct investment (OFDI) by firms from emerging countries. Based on an extensive coverage of studies published over a period of nearly 25 years between 1993 and 2017, we review extant research on this phenomenon from mainly China, as well as other emerging countries. We identify advances and analytical areas of OFDI research and pinpoint the key theories, methodologies, observed characteristics and the variables that have been examined in this growing research literature. Many areas of the above research themes remain underexplored, despite recent significant advancements, and may provide directions for future research.